2022
DOI: 10.1088/1748-9326/ac8068
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning based classification of atmospheric circulation types over Europe: projection of future changes in a CMIP6 large ensemble

Abstract: High- and low pressure systems of the large-scale atmospheric circulation in the mid-latitudes drive European weather and climate. Potential future changes in the occurrence of circulation types are highly relevant for society. Classifying the highly dynamic atmospheric circulation into discrete classes of circulation types helps to categorize the linkages between atmospheric forcing and surface conditions (e.g. extreme events). Previous studies have revealed a high internal variability of projected changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…During the review process of this study, an article from Mittermeier et al (2022) was published that analyzed, among other questions, CT frequency changes in the SMHI-LENS SSP370 scenario over a large Europe-North Atlantic domain. Their results are consistent with our finding that the frequency of some CTs changes significantly under future climate change.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the review process of this study, an article from Mittermeier et al (2022) was published that analyzed, among other questions, CT frequency changes in the SMHI-LENS SSP370 scenario over a large Europe-North Atlantic domain. Their results are consistent with our finding that the frequency of some CTs changes significantly under future climate change.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Details, however, differ from their as well as from other studies that analyze future circulation changes. For example, Huguenin et al (2020) find no change in any summer and winter CT frequencies towards the end of the twenty-first century, but their focus is on Central Europe and, probably more important in this context, they use a different classification method, namely the Grosswettertypes (GWT) classification method which was also applied in Mittermeier et al (2022). GWT groups the large-scale pressure fields mainly based on their predominant flow direction and basically does not take into account the pressure gradient magnitude which limits its efficacy in separating effects of CTs on other variables such as temperature and precipitation (Hansen and Belušić 2021).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They used their trained neural networks ensemble to analyse future changes in a single-model initial-condition large ensemble of the global climate model EC-Earth3 under the Shared Socio-Economic Pathways (Riahi et al, 2017) 3-7.0 scenario. Mittermeier et al (2022) demonstrated the enhanced capabilities of neural networks in classifying Großwetterlagen. However, the occurrence rate of Cyclonic Westerly was strongly underestimated by their networks.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have previously focused on the automatic classification of Großwetterlagen, namely James (2007) and Mittermeier et al (2022). James (2007) proposed an objective classification based on composite plots, whereby a circulation type was assigned to each day based on the composite with the highest correlation after temporal smoothing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation